A smartphone application for learning Arabic vocabulary: a comprehensive systematic review - Ab. Rahim, Rosyawati; Ismail, Taufik; Abu Bakar, Radhwa; Mustafa, Wan Azani (Global Academic Excellence (M) Sdn Bhd (GAE), 2024)
The drastic technological advancement has paved the way for innovative approaches to language learning, with smartphone applications emerging as powerful tools in education. This systematic review explores the design and evaluation of a smartphone application that enhances Arabic vocabulary acquisition. Numerous language learning applications exist. Nevertheless, a gap exists in the literature regarding the specific design elements and evaluation criteria tailored for Arabic vocabulary acquisition. This review addresses the lack of a consolidated understanding of the challenges and opportunities in developing a smartphone application dedicated to learning Arabic vocabulary. This comprehensive systematic review explores the design and evaluation of smartphone applications dedicated to enhancing Arabic vocabulary acquisition, employing advanced search techniques on Scopus and Eric databases with keywords “smart phone,” “Arab,” and “vocabulary.” The flow of the study is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The final primary data (n = 28) articles were identified, clustering around three main themes: (1) Language Skills and Comprehension in Bilingual Contexts, (2) Technology and Language Learning, and (3) Corpus and Text Analysis. This systematic review contributes to the academic discourse by highlighting the current landscape and paving the way for future research in the dynamic intersection of technology and Arabic language education. This systematic review sheds light on the current landscape of smartphone applications designed for learning Arabic vocabulary. The findings from this review are expected to inform educators, developers, and policymakers, ultimately contributing to improving Arabic language education through innovative technological solutions.